Analysis of Student Satisfaction Levels with Multimedia Services Sepuluh Nopember Institute of Technology (ITS) Library Using the Libqual+TM - Tondo Indra Nyata; Lolytasari Lolytasari (Universitas Terbuka, 2024)
This study aims to analyze student satisfaction with multimedia services at the Sepuluh Nopember Institute of Technology (ITS) Library using the LibQUAL+TM indicator. LibQUAL+TM is a tool developed by the Association of Research Libraries (ARL) to assess user perceptions of library service quality. The research method used is quantitative with a survey approach. The research instrument was an online questionnaire developed based on three dimensions of LibQUAL+TM: the effect of service, information control, and Library as place. Data were collected from a sample of ITS students who used the Library's multimedia services in 2023. The analysis showed that overall, students were